A comparative study of death anxiety and death attitudes in Han and Tibetan ethnic groups. Issue 5 (28th May 2022) - Yin, Fang; He, Yiqing; He, Yu; Shen, Heyong; Ip, Kuaipeng
Abstract: This study compared the responses of 380 Han and 315 Tibetan respondents regarding their attitudes about death and factors influencing those attitudes using the Death Anxiety Scale and Death Attitude Profile-Revised . The results show that Tibetan respondents expressed more death anxiety, fear of death, death avoidance, and escape acceptance than the Han participants, while Han participants showed more neutral acceptance than the Tibetan participants. There was a significant interaction between age and gender around Approaching Death. In addition, the death attitudes of Han and Tibetan participants were influenced by religious beliefs, funeral experiences, and the way their families talked about death.